Late Holocene volcanic activity and environmental change in Highland Guatemala. (1st July 2018) - Lohse, Jon C.; Hamilton, W. Derek; Brenner, Mark; Curtis, Jason; Inomata, Takeshi; Morgan, Molly; Cardona, Karla; Aoyama, Kazuo; Yonenobu, Hitoshi
Abstract: We present a record of late Holocene volcanic eruptions with elemental data for a sequence of sampled tephras from Lake Amatitlan in Highland Guatemala. Our tephrochronology is anchored by a Bayesian P_Sequence age-depth model based on multiple AMS radiocarbon dates. We compare our record against a previously published study from the same area to understand the record of volcanism and environmental changes. This work has implications for understanding the effects of climate and other environmental changes that may be related to the emission of volcanic aerosols at local, regional and global scales. Highlights: Late Holocene volcanic activity in Highland Guatemala was episodic. Elemental data from multiple tephras are presented and compared with published source data to identify sources of eruptions. Sequence is controlled by Bayesian age-depth model. Volcanism did not seriously affect regional populations, as opposed to Late Formative mega-droughts, but may have exacerbated drought recoveries in the case of Ilopango.